An Analysis of Reading Comprehension Exercises in the English on Target Textbook for Indonesian Senior High Schools - Geby Marpaung; Frendi Lumbantoruan; Ramayani Silalahi; Bill Sibarani; Erikson Saragih; Parlindungan Purba (English Lecturers and Teachers Association (ELTA), 2026)
This study investigates the reading comprehension exercises presented in the English on Target textbook published by Erlangga for Grade XI Indonesian senior high school students. Employing a descriptive qualitative research design, the study analyzes all reading passages and accompanying comprehension tasks across eight chapters of the textbook. Document analysis was used as the primary data collection technique, focusing on the cognitive demands of each reading question. Bloom’s Revised Taxonomy served as the analytical framework to categorize reading comprehension questions into lower-order and higher-order thinking skills, including remembering, understanding, applying, analyzing, and evaluating. The findings reveal that the textbook addresses six major reading comprehension skills: identifying main ideas, locating specific information, understanding vocabulary in context, making inferences, identifying authorial purpose, and recognizing text organization. Literal comprehension tasks, particularly those requiring factual recall and identification of explicit information, dominate the early chapters. However, inferential and evaluative questions appear more frequently in later units, indicating a gradual progression toward higher-order thinking skills. In terms of exercise formats, five main types were identified: multiple-choice questions, vocabulary-based items, true/false and matching tasks, open-ended comprehension questions, and grammar-integrated reading activities. Multiple-choice exercises constitute the majority of tasks, while open-ended and evaluative questions are less frequent. Although the textbook demonstrates an effort to scaffold students’ reading development from basic comprehension to more complex cognitive engagement, lower-order thinking skills remain predominant. These findings suggest that teachers may need to supplement the textbook with additional inferential and evaluative reading activities to better support higher-order literacy development in Indonesian EFL classrooms. Keywords : Reading Comprehension; Textbook Analysis; English on Target; Reading Exercises; EFL Literacy